Improvement of mechanical properties of polycaprolactone (PCL) by addition of nano-montmorillonite (MMT) and hydroxyapatite (HA) - Abdul Haq, Reazul Haq (Trans Tech Publications Inc, 2013)
For many years, researcher have focused on developing a medical part of human body from polymer as to replace metal. This report described the mechanical characteristic of biodegradable Polycaprolactone (PCL) blend with nanoMontmorillonite (MMT) and Hydroxyapatite (HA). The amount of nanoMMT is varies from 2 to 4 by weight % meanwhile the amount of HA is fixed to 10 by weight percentage (wt %). The addition of nanoMMT and HA filler is to tune and indirectly improve the mechanical properties of PCL. These are proven by carrying out the tensile, and also flexural test for samples which is injected from injection molding machine. Both the tensile and flexural test are conducted using Shimadzu AG-I Unversal Testing Machine with 10kN capacity. From the analysis it is found that overall PCL/MMT/HA composites gives better result in both tensile and flexural analysis compare to PCL/MMT composite. PCL/MMT/HA composite with 2 wt% of MMT and 10 wt% of HA have indicated the highest tensile modulus, meanwhile PCL/MMT/HA composite with 4 wt% MMT and 10 wt% HA have plotted the highest flexural strength and modulus value